2018
DOI: 10.24913/rjap.20.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Self-Esteem and Tendency of Bullying among Primary School Children

Abstract: In this exploratory research, a mixed method research design was used to understand how primary school children perceive bullying behaviour and to uncover the extent of self-esteem on their bullying experiences. Two hundred and eighty participants took part in a survey of their bullying behaviour and self-esteem. Additionally, semi-structured interviews were conducted with 6 children. Survey findings indicated that higher self-esteem leads to higher bullying behaviour. Further analyses within sub-samples defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
0
4
1
Order By: Relevance
“…Boys are more exposed to bullying than girls. This result is inconsistent with the studies of [22,23]. Girls are more exposed to bullying than boys, which leads to negative outcomes, such as truancy from school, low academic achievement, and low self-esteem.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Boys are more exposed to bullying than girls. This result is inconsistent with the studies of [22,23]. Girls are more exposed to bullying than boys, which leads to negative outcomes, such as truancy from school, low academic achievement, and low self-esteem.…”
Section: Discussioncontrasting
confidence: 78%
“…The age group of 10-11 years is more exposed to bullying than the age group of 12-13 years. Young children are affected by bullying more than those older than them due to immaturity, and thus their self-view is affected and a lack of self-confidence begins, and a strong correlation is observed between bullying and lack of self-confidence among children [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, that there was a statistical highly significant relation was found between the sociodemographic characteristics and prevalence of bullying among the studied group at p< 0.01. On the other hand, result for Ang et al (2018) [9] which studied self-esteem and tendency of bullying among primary school children and reported that in relation to the male gender, it was observed that the victims have mean low self-esteem, finally confirmed that there was a relationship between gender and self-esteem, and especially males have lower self-esteem. In the researcher point of view, male gender is more prone to all types of bullying which indirectly relate to self-esteem.…”
Section: Discussionmentioning
confidence: 94%
“…Although peer aggression usually peaks in early adolescence ( Perry et al, 1988 ), forms of bullying can also occur in primary school, and some studies have found certain gender differences in the prevalence of involvement. In particular, males appear to be at heightened risk of being involved in bullying, both as bullies and as victims, while females tend to report more often forms of indirect victimization ( Iossi Silva et al, 2013 ; Ang et al, 2018 ; Twardowska-Staszek et al, 2018 ; Jiménez, 2019 ) and are more likely to engage in forms of indirect bullying such as active social exclusion ( Ang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%